Bhartr̥hari, language, thought and reality : proceedings of the international seminar, Delhi, December 12-14, 2003 - Caturvedī, Mithileśa (Motilal Banarsidass Publishers, 2009)
Contributed research papers presented at three day International Seminar on Bhartr̥hari: Language, Thought, and Reality at the India International Centre, New Delhi on Dec. 12-14, 2003 organised as part of the centenary celebration of Motilal Banarsidass.